Focal Segmental Glomerulosclerosis Preceding Type 2 Papillary Renal Cell Carcinoma - Dominik Dabrowski; Ekin Ozluk; Silvia Barbeito; Eric X. Wei (Case Reports in Pathology)
Renal cell carcinoma (RCC) is the predominant renal malignancy in adults. Of the four general subtypes, papillary renal cell carcinoma (P-RCC) is the second most common and can be subdivided into type I, type II, and a mixture of type I and II. Focal segmental glomerulosclerosis (FSGS) is the most common glomerulopathy at all ages, and it can be seen as a paraneoplastic syndrome. RCC, in general, is known to present with many paraneoplastic syndromes, and glomerulopathies are among these. Rarely, RCC and glomerulopathies may overlap in the same patient. Here, we report a 58-year-old male with a past medical history of FSGS and chronic kidney disease (CKD), stage III, who was found to have an incidental renal mass that was later diagnosed as type II P-RCC. The histology showed pseudostratified tumor cells with an eosinophilic cytoplasm that formed papillary configurations and displayed areas of necrosis. The prior FSGS diagnosis exhibited segmental sclerosis, refractory tufts, and capillary membrane wrinkling. A period of 1.5 years elapsed between the diagnosis of the glomerulopathy and the malignancy. The tumor was found to be at stage TIb. To our knowledge, this may be the first reported case of usual-type FSGS as paraneoplastic glomerulopathy (PG) preceding P-RCC. Because FSGS only sparingly affects the kidney and is a common glomerulopathy in adults, it is reasonable to complete comprehensive diagnostic studies and commence medically necessary treatment, especially in the background of other renal comorbidities. These preexisting comorbidities may be associated with malignancy very early in its course. The probability of RCC-associated paraneoplastic glomerulopathy is low, which means an already incidentally found renal mass may conceal a serpentine paraneoplastic syndrome. A more developed understanding of these manifestations can lead experienced clinicians to suspect and possibly uncover an insidious RCC before it advances.